(untitled) (World Economics and Finance Bulletin, 2022)
This article considers the assessment of the competitiveness of the enterprise by the type of market, competitors producing substitute goods, analysis, product quality, prices, sales channels, advertising, as well as a list of major importers of these goods in the country.